Uncertainties in coaxial cable transfer impedance - Lansink Rotgerink, J.H.G.J.; Verpoorte, J.; Schippers, H. (IEEE, 2018)
The Electro-Magnetic Compatibility (EMC) design of aircraft and spacecraft has to consider the shielding effectiveness of metal braids around wires and cable bundles. The EMC design is usually supported by modeling and measurement of the transfer impedance of representative samples of metal braids. In practice it turns out that results of modeling tools and measurements are not always in good agreement, in particular for the higher frequencies in the MHz region. It appears that both modeling tools and measurement methods are subject to uncertainties. The objective of the present paper is to investigate these uncertainties. Therefore, a sensitivity analysis is applied to an analytical transfer impedance model. Results indicate that the determination of the average height between the carriers of a braided shield is a critical quantity to obtain accurate transfer-impedance predictions at high frequencies. Moreover, a multi-conductor transmission line (MTL) model for the line injection method as set-up for transfer impedance measurements is presented. This MTL model is used to analyse the sensitivity of termination loads and permittivities, and to show the differences in resonance effects on transfer impedance measurements caused by impedance mismatches and by differences in propagation speeds inside and outside the coax under test. Finally, uncertainties in the measurement set-up are discussed. Finally, uncertainties in the measurement set-up are discussed. Finally, uncertainties in the measurement set-up are discussed.